Anti-bacterial and anti-ulcer activity of selected Malaysian medicinal plants / Nurul Asyikin Othman - Othman, Nurul Asyikin (2012)
An impressive number of medicinal plants contains high amount of flavonoids and antioxidant compound which are very useful as they promotes anti-inflammatory, anti-bacterial and various therapeutic values. Antibiotic resistance in human pathogens due to increasing abuse of drugs has reached an alarming stage. The options in combating multiple drug resistance organisms are decreasing. Besides that, gastric ulcer has become a major problem worldwide. Acid, peptic activity and collapse of mucosal defense mechanism has been proven to be the pathological process in the formation of gastric ulcer. Proton-pump inhibitors have been introduced as the treatment. However, long term use of these drugs has been proven to cause various adverse effects. Hence, there is a need to develop new antimicrobial and antiulcer drugs. The purpose of this study was to investigate the antimicrobial and anti-ulcer activities of selected Malaysian medicinal plants in vitro. The medicinal plant extracts were tested by in vitro antibacterial test against six bacterial species, both Gram positive and Gram negative organisms. Disc diffusion assay was employed for assessing antimicrobial activity. The ethanol-induced gastric ulcer method in laboratory animals was used to determine anti-ulcer activity of the plants. Screening for antioxidant levels has also been carried out on the plant extracts. From this study, all plants were showed to have antibacterial activities within them except for Swietenia macrophylla. However, for antiulcer studies, all plants showed high antiulcer activity. As for the antioxidant screening, only two of the plants used were high in antioxidant level whereas the other two were not.